Cucurbit[8]uril-based supramolecular nanocapsules with a multienzyme-cascade antioxidative effect. Issue 92 (30th October 2019) - Liu, Shengda; Tian, Ruizhen; Xu, Jiayun; Wang, Liang; Sun, Jianxin; Jiang, Xiaojia; Wang, Tingting; Li, Xiumei; Luo, Quan; Liu, Junqiu
Abstract : Supramolecular nanocapsules with both SOD and GPx activities were constructed by the ternary host–guest complexation of azobenzene (Azo) and methylviologen (MV) to cucurbit[8]uril (CB[8]) and the subsequent self-assembly. Abstract : A supramolecular nanocapsule was constructed by the ternary host–guest complexation of azobenzene (Azo) and methylviologen (MV) to cucurbit[8]uril (CB[8]) and the subsequent self-assembly. The supramolecular nanocapsule with both glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities can mimic the intracellular enzymatic reactive oxygen species (ROS) defense system.